Analisa Pembayaran Perkuliahan Dengan Virtual Account Pada Universitas Raharja - Padeli Padeli; Eduard Hotman Purba; Bonari Simanjuntak (UNIVERSITAS RAHARJA, 2020)
In the academic world, every educational institution must have a tuition payment system, and with the rapid technological advances nowadays, educational institutions are required to create systems that are effective and efficient and relevant to current technology which will make it superior in competition within the scope of relevant agencies. At Raharja University, lecture payments still use a conventional system where transfer students and campus staff check which is considered less efficient. In this study, the writer uses a SWOT analysis between the virtual account payment system and the running system. The purpose of this study is to recommend the use of a Virtual Account in the payment of lectures at Raharja University. This research is expected to be a problem solving alternative that makes it easier for students to make financial payments, as well as facilitate campus monitoring of campus payments.